Sanctuary Cities: Public Attitudes Toward Enforcement Collaboration Between Local Police and Federal Immigration Authorities. Issue 1 (January 2020) - Casellas, Jason P.; Wallace, Sophia Jordán
Local law enforcement has dramatically increased its cooperation with federal immigration enforcement, while other localities refuse to cooperate. Although scholars have examined how sanctuary cities may differ from other places in terms of crime rates, attitudes toward local law enforcement's collaboration with federal immigration authorities remain understudied. We utilize original data from the 2016 Cooperative Congressional Election Survey (CCES) to study attitudes toward local/federal collaboration. Our results demonstrate that those who most recognize the racial advantage of Whites are significantly less likely to support collaboration between local police and federal authorities. Confirming prior work, our results also support the critical role of partisanship, nativity, and education in explaining attitudes toward sanctuary policies. Our findings have important implications for understanding attitudes toward immigration enforcement and policies.